Comparison of oxidative damage in Malaysian end-stage renal disease patients with or without non-insulin-dependent diabetes mellitus - Kuppusamy, U.R.; Indran, M.; Ahmad, T.S.; Wong, S.W.; Tan, S.Y.; Mahmood, A.A. (Elsevier, 2005)
Background: Comparisons of oxidative indices and total antioxidant status between end-stage renal disease (ESRD) patients with or without diabetes is scant, especially in the Asian population.